Quality Of Service Improvement With 802.11e Edca Scheme Using Enhanced Adaptive Contention Window Algorithm - Susan Prasetya; Basuki Rahmat; Erwin Susanto (eProceedings of Engineering, 2015)
Users of data services is growing exponentially and the content accessed by the users are mostly real time and multimedia communications. The most connection commonly used is wireless LAN IEEE 802.11. Quality of Service (QoS) is a mandatory requirement in Wifi to support network limited capacity. IEEE 802.11e introduce a new standard of QoS which is called Enhanced Distributed Channel Access (EDCA). This standard has gave a new method for QoS support compared with previous method called Distributed Coordination Function (DCF). EDCA scheme provide four type of traffic (background task, best effort, video and voice) which is called Access Category (AC) to define the priority. There are three main parameters in EDCA to improve Quality of Service i.e TXOP (Transmission Opportunity), AIFS (Arbitrary Inter Frame Space) and CW (Contention Windows). Based on the main reference for throughput and delay improvement, this research will focus on contention window adjustment. Adjustment depends on number of stations involved in the network and collision probability. The more number of stations or the lower contention window value will result higher collision probability. To validate the result of contention window adjustment, simulation using NS-2 is applied. Simulation is done during low traffic (non-saturated) and high traffic (saturated) network. The proposed algorithm leads the throughput improvement by 2.29% and delay improvement by 3.32% in average for all traffic category. Index Terms—Wifi, Qos, 802.11e, contention window, collision probability.